Urinary total 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanonol is positively associated with tooth loss - Lin Niu; Yuwei Zhang; Hu Zhu; Yue Jia; Changjie Sun; Yifei Zhang; Xuefei Sun; Zhaojing Ding; Jingning Gou; Luming Wang; Rui Zou; Shaojie Dong (BMC Public Health)
Abstract Background/aim Epidemiological studies had confirmed a fundamental association between smoking and tooth loss, but it remains unclear whether metabolites of tobacco products such as total 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanonol (TNNAL) play a role in the incidence and progress of tooth loss. This study aims to investigate the relationship between TNNAL and tooth loss as well as how systemic inflammatory indexes mediate this process. Methods The cross-sectional study data were collected from the National Health and Nutrition Examination Survey conducted in the United States. After screening and comparing the baseline data, zero-inflated negative binomial regression models were utilized to evaluate the relationship between urinary TNNAL level and missing teeth among whole population and participants with different smoking status. Furthermore, bootstrapping was applied to test the mediation effect of systemic inflammatory indexes between TNNAL level and missing teeth. Results 7726 participants were included, having 2958 individuals belonging to the TNNAL = 0 group and 4768 in the TNNAL > 0 group. In the model with covariates fully adjusted (model 3) among whole population, TNNAL level was found to be positively correlated with tooth loss [Incidence Rate Ratio (IRR) = 1.107, 95% confidence interval (95% CI) = 1.074–1.140], especially in the fourth quartile (Q4) of TNNAL level (IRR = 1.715; 95%CI = 1.535–1.916) compared to the Q1. Red blood cell distribution width (RDW) and monocyte/highdensity lipoprotein cholesterol ratio (MHR) played partial mediating role in the association between TNNAL and tooth loss, and the indirect effect of each was 0.0242 (RDW, 95%CI = 0.0076–0.0612) and 0.0151 (MHR, 95%CI = 0.0034–0.0426), respectively. The mediating effect was 0.393 (95%CI = 0.0179–0.958). In the regression model 3 among group of TNNAL > 0, higher concentration of urinary TNNAL was associated with increasing tooth loss (IRR = 1.079, 95%CI = 1.047–1.112). When group of TNNAL > 0 was further divided into subgroups according to the smoking status, a positive correlation was found between TNNAL and missing teeth among current active-smokers (Model 3: IRR = 1.508, 95%CI = 1.341–1.696), as well as passive former-smokers (Model 3: IRR = 1.127, 95%CI = 1.021–1.243). Conclusions Our study revealed a positive relationship between urinary TNNAL and tooth loss, and further demonstrated the mediating role of RDW and MHR between the TNNAL and the number of missing teeth in the whole popualtion. These findings will provide new theoretical insights for policy formulation and clinical therapeutic for the target prevention and intervention of related diseases.